Double-Layer Precoder and Cluster-Based Power Allocation Design for LEO Satellite Communication With Massive MIMO - Yue, Tong; Liu, Aijun; Liang, Xiaohu (IEEE communications letters, 2023)
In this work, we propose a double-layer precoder and cluster-based power allocation design for low earth orbit (LEO) satellite communication with massive multiple input multiple output (MIMO). Specifically, spectral efficiency (SE) is chosen as the evaluation metric with hardware complexity, transmit power, instantaneous channel state information (iCSI) and statistical channel state information (sCSI) considered. We simplify the three-dimension (3D) air-to-ground MIMO channel under satellite environment with the angular spread model. Then, a double-layer precoder is proposed to reduce the hardware complexity and eliminate the inter-user interference (IUI) among each user cluster. With angle of departure (AoD) information, the user clustering criteria to maximize the SE and eliminate inter-cluster interference (ICI) is derived. After that, a cluster-based power allocation scheme is proposed by dividing the total transmit power into two parts, one to meet the user's minimum service requirement and the other to get optimal SE performance by waterfilling algorithm. Simulation results show that the proposed scheme achieves better SE performance compared with other feasible approaches.